SYNTHESIS METHOD OF THE FUNCTIONAL STRUCTURE HYDRAULIC SYSTEMS - B. K. Grankin; V. V. Kozlov (Научный вестник МГТУ ГА, 2016)
The synthesis method of the functional structure hydraulic systems are deal with in the paper. The method is based on the representation of synthesis objects as a control system in relation to the working environment as an object management. Synthesis provides the procedures for formalizing the functional requirement in a matrix of numerical codes and their decomposition to the level of function elements. The method is addressed to specialists in computer-aided projecting of hydraulic systems for various applications, including systems of water supply, refueling, fire systems, etc.